CONSTRUCTION THE BRIDGE PIER AS PARAMETRIC OBJECT USING AUTODESK REVIT - Hladka, K. I.; Bocharova, N. P. (Science and Transport Progress, 2017)
Purpose. The work is aimed to solve the following tasks: 1) to investigate the possibilities of Autodesk Revit to create parametric objects; 2) to create an information model of the bridge pier with the possibility of changing the model size without changing geometry of the object; 3) to trace the complexity and feasibility of using parametric models when designing the elements of bridges. Methodology. The studies were carried out using spatial modeling in the Autodesk Revit system. The ratio of the parameters of the object was set, the relationship between individual geometric elements was determined and the changes that were made to the model with the change of the specified parameters were checked. Findings. Support model of two types has been created: for railway bridges and for road bridges. Both types of models change the dimensions and the number of constituent elements in accordance with the entered parameters. The performed work confirms the possibility of creating information parametric models of complex form and the expediency of using them in the design of bridges and not only. Originality. Creation of information models is a modern and relevant topic. But both in the literature and in Internet resources, parametrization is considered on the example of simple objects. The model proposed in the article consists of several dependent geometric bodies; therefore, it opens the topic of objects parameterization more fully and in detail, in comparison with the existing sources. As for the creation of parametric models of the bridge elements - such information is not found in the literature, that is, it is proposed for the first time. Practical value. Parametrization of spatial models allows significantly to accelerate and simplify the process of designing any objects due to the use of typical parametric models in many projects. Especially it concerns the design of bridges, since the standard elements for them, such as support or span are not yet presented in software products. Designing the bridges as a flat contour, in comparison with the use of spatial information models, is a long and inefficient process, besides it does not allow visualization, which is a necessary component of any project.